Building academic language meeting common core standards across disciplines, grades 5-12 - Zwiers, Jeff (San Francisco, CA Jossey-Bass, a Wiley Brand, 2014)
"The introductory pages of the Common Core State Standards call for the following distributions of text: 50% literary/50% information (4th grade); 45% literary/55% information (8th grade); 30% literary/70% information (12th grade). This is a major shift in encouraging teachers to get students understanding and using more academic language as they progress through middle and high school. Many students today, whether they are native English speakers or recent immigrants, need help in understanding and using the language of academic learning. An essential resource for teaching all students, this book explains what every teacher needs to know about language for supporting reading, writing, and academic learning. Based on theory, research and practice, it includes activities, exercises, and practical strategies for building vocabulary, grammar, and language learning approaches routinely into math, science, history, and language arts lessons.This second edition includes new strategies to address specific standards and answers key questions about reading across content areas, including:--What is academic language and how does it differ by content area?--How can language-building activities support content understanding?--How can students be assisted in using language more effectively?--How can academic language usage be modeled routinely in the classroom?--How can lesson planning and assessment support academic language development? "--
Includes bibliographical references and index
1
Keywords: Academic language -- Study and teaching; EDUCATION / Teaching Methods & Materials / General